Gamma transcranial alternating current stimulation increases segregation in the sensorimotor network - Cataneo, Antonio; Marino, Marco; Manzo, Nicoletta; Scarpazza, Cristina; Arcara, Giorgio; Mapelli, Daniela; Masina, Fabio (Frontiers in Psychology, 2026)
IntroductionTranscranial alternating current stimulation (tACS) has emerged as a promising tool to modulate brain dynamics, especially in the context of motor recovery in clinical populations. Yet, its network-level effects on the sensorimotor (SM) functional organization have only been partially explored. In this study, we investigated whether gamma-frequency tACS can modulate functional connectivity and enhance segregation within the SM network, which is an index typically associated with better motor performance.MethodsIn a within-subject, sham-controlled design, EEG was recorded before and after gamma tACS in 34 healthy subjects. Functional connectivity was quantified across three SM sub-networks, according to Yeo’s parcelation, in five frequency bands, including delta, theta, alpha, beta, and gamma, using intra- and inter-network connectivity (IntraNC and InterNC, respectively) measures. ANCOVA tests were performed on IntraNC and InterNC values for each frequency band, to compare the sham and real condition at post p-stimulation hase. The connectivity values of the pre-stimulation phase were used as a covariate, to account for state-dependent effects.ResultsWe did not find a significant interaction with time and condition. However, post hoc analyses showed significant interactions for IntraNC following real, but not sham, tACS (p = 0.029, FDR-corrected). Furthermore, we reported increased segregation post-tACS in specific SM sub-networks for alpha and beta frequency bands, primarily driven by enhanced IntraNC. No effects were observed in delta or theta frequency bands.DiscussionAlbeit we did not find significant interactions of time and stimulation condition, additional analyses showed that gamma tACS might selectively modulate oscillatory dynamics within SM sub-networks, enhancing functional segregation in a frequency-specific manner. Given the roles of alpha/beta in sensorimotor integration and gamma in local processing, these effects might reflect more efficient neural communication. Our results support the potential of tACS as a neuromodulatory intervention to target dysfunctional network interactions in clinical populations.